Islamic philosophy A-Z - Groff, Peter S.; Leaman, Oliver, 1950- (Edinburgh : Edinburgh University Press, 2007)
These thorough, authoritative yet concise alphabetical guides introduce the central concepts of the various branches of philosophy. Written by established philosophers, they cover both traditional and contemporary terminology.
Cover -- COPYRIGHT -- Contents -- Series Editor's Preface -- Introduction -- Using This Book -- Acknowledgements -- Islamic Philosophy A-Z -- Bibliography -- Last Page.
Includes bibliographical references (pages 217-237).
Print version record.
Master record variable field(s) change: 072
Keywords: Islamic philosophy -- Encyclopedias; Islamic philosophy -- History; Islamic philosophy -- Terminology; PHILOSOPHY -- Eastern; Islamic philosophy; Islamische Philosophie; RELIGION / Islam / General; Electronic books; Encyclopedias; History; Terminology